PENGARUH PENDAPATAN, UMUR DAN DANA KELANGSUNGAN TERHADAP KEPUTUSAN PEMAKAIAN JASA ASURANSI JIWA PADA AJB BUMIPUTERA 1912 KANTOR CABANG BATURAJA - Hema Malini; Devi Novia Utami Putri; Rini Apriyani (KOLEGIAL, 2021)
The purpose of this study was to determine the effect of income, age and continuity funds on the decision to use life insurance services at AJB Bumiputera 1912 Baturaja Branch Office. The method used in this research is descriptive method and by using incidental sampling with a sample of 60 respondents and this study uses qualitative and quantitative analysis techniques. The results of this study indicate that based on the partial test there is no effect of income (X1) and age (X2) on the decision to use life insurance services at AJB Bumiputera 1912 Baturaja Branch Office, while continuity funds have an effect. Simultaneously there is an effect of income, age and continuity funds on the decision to use life insurance services at AJB Bumiputera 1912 Baturaja Branch Office.